A combined teamwork training and work standardisation intervention in operating theatres: controlled interrupted time series study. Issue 2 (22nd July 2014) - Morgan, Lauren; Pickering, Sharon P; Hadi, Mohammed; Robertson, Eleanor; New, Steve; Griffin, Damian; Collins, Gary; Rivero-Arias, Oliver; Catchpole, Ken; McCulloch, Peter
Abstract : Background: Teamwork training and system standardisation have both been proposed to reduce error and harm in surgery. Since the approaches differ markedly, there is potential for synergy between them. Methods: Design: Controlled interrupted time series with a 3 month intervention and observation phases before and after. Setting: Operating theatres conducting elective orthopaedic surgery in a single hospital system (UK Hospital Trust). Intervention: Teamwork training based on crew resource management plus training and follow-up support in developing standardised operating procedures. Focus of subsequent standardisation efforts decided by theatre staff. Measures: Paired observers watched whole procedures together. We assessed non-technical skills using NOTECHS II, technical performance using glitch rate and compliance with WHO checklist using a simple quality tool. We measured complication and readmission rates and hospital stay using hospital administrative records. Before/after change was compared in the active and control groups using two-way ANOVA and regression models. Results: 1121 patients were operated on before and 1100 after intervention. 44 operations were observed before and 50 afterwards. Non-technical skills (p=0.002) and WHO compliance (p<0.001) improved significantly after the intervention in the active versus the control group. Glitch count improved in both groups and there was no significant effect on clinical outcomes. Discussion: Combined training in teamwork and system improvement causes marked improvements in team behaviour and WHO performance, but not technical performance or outcome. These findings are consistent with the synergistic hypothesis, but larger controlled studies with a strong implementation strategy are required to test potential outcome effects.